2009
DOI: 10.1111/j.1540-8191.2008.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy: How and When Should It Be Done in Cardiovascular Surgery ICU?

Abstract: Background: The aim of this study was to assess the effect of timing and techniques of tracheostomy on mortality and morbidity in cardiovascular surgery patients. Methods: Between January 2000 and October 2007, a total of 19,559 cardiac and vascular operations were performed in our hospital, and 205 of these patients (1.04%) who underwent a tracheostomy procedure were included in this retrospective study. Results: Surgical tracheostomy (ST) was employed in 134 (65.4%) and percutaneous tracheostomy (PT) in 71 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 18 publications
5
31
0
Order By: Relevance
“…Yavas et al published a single centre review of 205 patients and found that ET was associated with earlier mobilization, earlier enteral feeding, lower incidence of infections, and lower mortality. Furthermore, this study confirmed that percutaneous tracheostomy performed after the cardiac surgical procedure did not increase the incidence of sternal osteomyelitis and sternal wound dehiscence [15]. Trouillet and colleagues conducted a prospective cohort study of 163 patients who were still mechanically ventilated 3 days after cardiac surgery.…”
Section: Discussionmentioning
confidence: 79%
“…Yavas et al published a single centre review of 205 patients and found that ET was associated with earlier mobilization, earlier enteral feeding, lower incidence of infections, and lower mortality. Furthermore, this study confirmed that percutaneous tracheostomy performed after the cardiac surgical procedure did not increase the incidence of sternal osteomyelitis and sternal wound dehiscence [15]. Trouillet and colleagues conducted a prospective cohort study of 163 patients who were still mechanically ventilated 3 days after cardiac surgery.…”
Section: Discussionmentioning
confidence: 79%
“…Recent work described an opposite picture; only a minority, 1.04% to 4.13% of patients underwent a tracheostomy, mostly performed at the bedside in a percutaneous approach. 3,4,[7][8][9][10][11][12][13][14] The overall survival rate is low in patients undergoing a tracheostomy after cardiac surgery. Walts et al 13 described a 1-year survival rate of 31%; Ballotta et al 2 described a 1-and 2-year survival rate of 29% and 31%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In any case the institutional protocols for prophylaxis were not changed during the study period and have guaranteed homogeneity of treatment among the study patients. The effect of dilatational percutaneous tracheostomy on the incidence of sternal wound complications should be addressed in dedicated investigations 13 …”
Section: Discussionmentioning
confidence: 99%